FEATURES OF BUSINESS COMMUNICATIONS IN THE SPHERE OF PUBLIC ADMINISTRATION - Viktoriia Andriiash; Svitlana Verba (Публічне управління та регіональний розвиток)
The article is devoted to the urgent problem of analyzing business communications at different levels of public administration as a way of improving the quality and accessibility of public services. Business communication is the basis of the vital activity of any structure, subdivisions, bodies that are components of the public administration system and represent public power. Business communications are necessary for the effective implementation of management decisions, feedback, adjustment of the goal and stages of the public administration system's activities, since communicative processes, explanations of policies, and actions of the authorities in general are sometimes uncertain, not systematized, spontaneous, and often unpredictable in terms of their course or consequences. Therefore, today there is a need for theoretical substantiation of the principles of communication in public administration, improvement of its internal and external vectors, development of effective methods and forms for the practical implementation of management functions. The features of communications in the public administration system are considered. It is emphasized that the communicative process plays an important role in public administration, regardless of the form of communication. It is found that the communication process in public administration includes the following elements: public administration institutions and citizens, messages, communication channels, information barriers, feedback. It is emphasized that for successful communication, it is not important how clearly and precisely the transmitted idea is formulated, but how much the interacting parties agree in its interpretations or not. Proposals are formulated to improve the implementation of business communications in the public administration system, in order to increase the efficiency of its functioning and establish effective interaction with society. It is proven that the implementation of effective business communications will stimulate the efficiency of the public administration system, its perception by society and increase the overall level of management activity.